Human cold habituation: Physiology, timeline, and modifiers. Issue 2 (3rd April 2022) - Yurkevicius, Beau R.; Alba, Billie K.; Seeley, Afton D.; Castellani, John W.
ABSTRACT: Habituation is an adaptation seen in many organisms, defined by a reduction in the response to repeated stimuli. Evolutionarily, habituation is thought to benefit the organism by allowing conservation of metabolic resources otherwise spent on sub-lethal provocations including repeated cold exposure. Hypermetabolic and/or insulative adaptations may occur after prolonged and severe cold exposures, resulting in enhanced cold defense mechanisms such as increased thermogenesis and peripheral vasoconstriction, respectively. Habituation occurs prior to these adaptations in response to short duration mild cold exposures, and, perhaps counterintuitively, elicits a reduction in cold defense mechanisms demonstrated through higher skin temperatures, attenuated shivering, and reduced cold sensations. These habituated responses likely serve to preserve peripheral tissue temperature and conserve energy during non-life threatening cold stress. The purpose of this review is to define habituation in general terms, present evidence for the response in non-human species, and provide an up-to-date, critical examination of past studies and the potential physiological mechanisms underlying human cold habituation. Our aim is to stimulate interest in this area of study and promote further experiments to understand this physiological adaptation.